The twelve knits of Christmas - Goble, Fiona (Andrews McMeel Publishing, LLC, 2012)
From a partridge in a pear tree to twelve drummers drumming, Goble brings the popular verse to life as knitters of all skill levels create each of the twelve characters featured in the charming holiday song. The characters make perfect gifts, stocking stuffers, ornaments, or toys for children as you teach them the words to this classic song.